Clinical Features and Pathological Mechanisms of Gout - Salkhidinovna, Bekmuradova Makhsuda; kizi, Fozilova Maftuna Kenja; Kahorovich, Husanov Sobitjon (American Journal of Biology and Natural Sciences, 2024)
Gout is a chronic inflammatory arthritis characterized by the accumulation of monosodium urate (MSU) crystals, leading to recurrent painful flares. This review explores the clinical features and pathological mechanisms of gout, highlighting the rising global prevalence due to dietary changes and metabolic disorders. A comprehensive literature review and meta-analysis were conducted to identify gaps in knowledge, particularly regarding the early diagnosis of asymptomatic hyperuricemia and personalized treatment strategies. Key findings indicate that genetic predispositions, dietary habits, and comorbidities such as chronic kidney disease significantly influence gout’s progression. The NLRP3 inflammasome plays a crucial role in mediating the inflammatory response to MSU crystals, triggering the release of pro-inflammatory cytokines like IL-1β. Despite advancements in understanding gout’s pathogenesis, significant knowledge gaps remain, particularly in non-Western populations and the long-term impacts of gout on quality of life. Implications of this research stress the necessity for early detection and tailored therapeutic approaches, emphasizing the integration of lifestyle modifications and pharmacological treatments. Future research should focus on developing sensitive biomarkers for early diagnosis and exploring the psychosocial and economic burdens of gout, ultimately aiming to enhance prevention and management strategies in diverse populations.